Arbitration Agreement in Taiwan Arbitration Regulations in a Comparative Perspective - Wan, Ju-Yeh (Indonesian Comparative Law Review, 2018)
As far as arbitration agreement is concerned, it is suggested that the Taiwan Arbitration Act1 (as last amended on 2 December 2015, formerly named the Commercial Arbitration Act, came into force on 24 December 1998, after the reform of the arbitration law in Taiwan.) is trying to meet the needs of further development of Taiwanese arbitration, particularly international commercial arbitration. Article 1, Article 2 and Article 3 of the Taiwan Arbitration Act set out some criterion on adjudicating the validity of an arbitration agreement. This thesis try to make a comparative study of the Taiwanese arbitration system with other arbitration systems from arbitration agreement perspectives and hope possibly to improve Taiwan Arbitration Law. Proceeding an arbitration should be based on a valid agreement to arbitrate. This comparative study focuses on the issue relating to arbitration agreement.